Whipple disease mimicking inflammatory bowel disease - Tatsuki, Maiko (Intest Res, 2021)
Whipple disease is a systemic chronic infection caused by Tropheryma whipplei. Although chronic diarrhea is a common gastrointestinal symptom, diagnosis is often difficult because there are no specific endoscopic findings, and the pathogen is not detectable by stool culture. We present a female patient with Whipple disease who developed chronic bloody diarrhea and growth retardation at the age of 4 years. Colonoscopy showed a mildly edematous terminal ileum and marked erythema without vascular patterns throughout the sigmoid colon and rectum. Subsequently, a primary diagnosis of ulcerative colitis was made. Histopathological analysis of the terminal ileum showed the presence of foamy macrophages filled with periodic acid-Schiff-positive particles. Polymerase chain reaction using DNA from a terminal ileum biopsy sample amplified a fragment of 16S rRNA from T. whipplei. Antibiotic treatment relieved the patient’s symptoms. There was no evidence of immunodeficiency in the present case. Since Whipple disease worsens after anti-tumor necrosis factor inhibitor therapy, considering this infection in the differential diagnosis may be important in patients with inflammatory bowel disease, especially before initiation of immunotherapy.